c - Alexander, Michael; Kusleika, Dick (Indianapolis, IN : Wiley, 2019)
Maximize your Excel experience with VBA Excel 2019 Power Programming with VBA is fully updated to cover all the latest tools and tricks of Excel 2019. Encompassing an analysis of Excel application development and a complete introduction to Visual Basic for Applications (VBA), this comprehensive book presents all of the techniques you need to develop both large and small Excel applications. Over 800 pages of tips, tricks, and best practices shed light on key topics, such as the Excel interface, file formats, enhanced interactivity with other Office applications, and improved collaboration features. Understanding how to leverage VBA to improve your Excel programming skills can enhance the quality of deliverables that you produce-and can help you take your career to the next level.-Explore fully updated content that offers comprehensive coverage through over 900 pages of tips, tricks, and techniques -Leverage templates and worksheets that put your new knowledge in action, and reinforce the skills introduced in the text -Improve your capabilities regarding Excel programming with VBA, unlocking more of your potential in the office Excel 2019 Power Programming with VBA is a fundamental resource for intermediate to advanced users who want to polish their skills regarding spreadsheet applications using VBA.
Introduction to Excel VBA. Essentials of Spreadsheet Application Development -- Introducing Visual Basic for Applications -- VBA Programming Fundamentals -- Working with VBA Sub Procedures -- Creating Function Procedures -- Understanding Excel's Events -- VBA Programming Examples and Techniques -- Advanced VBA Techniques. Working with Pivot Tables -- Working with Charts -- Interacting with Other Applications -- Working with External Data and Files -- Working with UserForms. Leveraging Custom Dialog Boxes -- Introducing UserForms -- Looking at UserForm Examples -- Implementing Advanced UserForm Techniques -- Developing Excel Applications. Creating and Using Add-Ins -- Working with the Ribbon -- Working with Shortcut Menus -- Providing Help for Your Applications -- Leveraging Class Modules -- Understanding Compatibility Issues -- Appendix: VBA Statements and Functions Reference.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed May 6, 2019)
John Wiley and Sons
Keywords: Microsoft Excel (Computer file); Microsoft Excel (Computer file); Visual Basic for Applications (Computer program language); COMPUTERS -- Desktop Applications -- Spreadsheets; Visual Basic for Applications (Computer program language)